Nano-hydroxyapatite-assisted enzyme-induced carbonate precipitation enhances Pb-contaminated aqueous solution and loess remediation - Bian, Zhao-Wei; Cheng, Wen-Chieh; Xie, Yi-Xin; Rahman, Md Mizanur; He, Wenjie (Frontiers in Bioengineering and Biotechnology, 2024)
Intensive agricultural activities could cause lead (Pb) bioaccumulation, threatening human health. Although the enzyme-induced carbonate precipitation (EICP) technology has been applied to tackle the aforesaid problem, the urease may denature or even lose its activity when subjected to a significant Pb2+ toxicity effect. To this end, the nano-hydroxyapatite (nHAP)-assisted EICP was proposed to reduce the mobility of Pb2+. Results indicated that a below 30% immobilization efficiency at 60 mM Pb2+ was attained under EICP. nHAP adsorbed the majority of Pb2+, preventing Pb2+ attachment to urease. Further, hydroxylphosphohedyphane or hydroxylpyromorphite was formed at 60 mM Pb2+, followed by the formation of cerussite, allowing hydroxylphosphohedyphane or hydroxylpyromorphite to be wrapped by cerussite. By contrast, carbonate-bearing hydroxylpyromorphite of higher stability (Pb10(PO4)6CO3) was developed at 20 mM Pb2+ as CO32- substituted the hydroxyl group in hydroxylpyromorphite. Moreover, nHAP helped EICP to form nucleated minerals. As a result, the EICP-nHAP technology raised the immobilization efficiency at 60 mM Pb2+ up to 70%. The findings highlight the potential of applying the EICP-nHAP technology to Pb-containing water bodies remediation.